Forming Character Through Buying and Selling Economic Activities for Grade 4 Elementary School Students at Jali Gayamharjo State Elementary School, Prambanan, Sleman Yogyakarta Academic Year 2022/2023 - Eva Vera Santi (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this research is to Form Character Through Buying and Selling Economic Activities in Grade 4 Elementary School Students at Jali Gayamharjo Public Elementary School, Prambanan, Sleman Yogyakarta Academic Year 2022/2023. The conclusion shows that buying and selling activities can strengthen the character of grade 4 students at SD Negeri Jali, Prambanan, Sleman, Yogyakarta for the 2022/2023 academic year.